Temporal Temples - Eric Carlson (Oz, 2007)
The concept of an eternal Architecture became institutionalized in the 1800s with the notion of “le chef d’oeuvre” or “the masterpiece,” which to this day still encumbers architects who strive to create works that remain unchanged and timeless.